Nonlinear modeling of unreinforced masonry structures under seismic actions: validation using a building hit by the 2016 Central Italy earthquake - Chiara Ferrero; Paulo Barbosa Lourenço; Chiara Calderini (Fracture and Structural Integrity)
A prolonged seismic sequence struck the regions of Central Italy between August 2016 and January 2017, causing several fatalities and widespread damage to the built environment. The main objective of this work was to study the structural and seismic behavior of “Pietro Capuzi” school, located in Visso, in the Marche region, which was severely damaged by the 2016-2017 Central Italy Earthquake. A 3D finite element (FE) model of the entire school was prepared, adopting a macro-modeling approach to represent masonry materials. An eigenvalue analysis was initially performed in order to identify the dominant modes of vibration of the structure and to calibrate the numerical model according to the results of the dynamic identification tests. Afterwards, nonlinear static analyses were performed on the calibrated FE model to evaluate the seismic response of the structure. Finally, the numerical results obtained in terms of crack pattern and failure mechanisms were compared with the damage experienced by the building. The numerical model proved to accurately predict the seismic response exhibited by the structure during the past seismic events.